Aplicações das radiações ionizantes na indústria alimentícia: sistema de inspeção de nível de enchimento - Fernandes, Marco Antonio Rodrigues [UNESP]; Carvalho, Everton Luiz de Abreu; Figueiredo, Lucas Raniel (My University, 2012)
The use of ionizing radiations has been growing in the last decades in all segments of activities such as: health, research and industry. In the industrial field of industry they are applied for inspection and quality control of materials, components and processes, investigating the sanity of control processes, without introducing any alterations in their characteristics. One of the main uses of these radiations in the industrial production line is the inspection, by gamma radiation, of stuffing level of liquids. This work presents the procedures of quality control of an irradiator used in the drinks industry and it highlights the performance of control mechanism studied in mechatronic engineering, introducing students to the concepts of industrial quality control automation.

O uso de radiações ionizantes tem crescido nas ultimas décadas em todos os segmentos de atividades, tais como: saúde, pesquisas e indústria. Na área industrial são aplicadas para inspeção e controle de qualidade de materiais, componentes e processos, investigando a sanidade dos processos de controle, sem, contudo introduzir quaisquer alterações nas suas características. Uma das principais utilizações destas radiações na linha de produção industrial é a inspeção, por radiação gama, de nível de enchimento de líquidos. Este trabalho apresenta os procedimentos de controle de qualidade de um irradiador utilizado na indústria de bebidas e realça a atuação de servomecanismos de controle estudados na engenharia de mecatrônica, introduzindo os estudantes nos conceitos de automação aplicados ao controle de qualidade industrial.
Applications of ionizing radiations in the food industry: inspection system of stuffing level
Keywords: Industrial processes; Ionizing radiations; Quality control; Stuffing level; Controle de qualidade; Nível de enchimento; Processos industriais; Radiações ionizantes